Sebuah Model Pemberdayaan Masyarakat di Kampung Tematik Mulyaharja Bogor Berbasis Pendampingan Perguruan Tinggi - Parantika, Asep; Wibowo, FX Setiyo; Wiweka, Kadek (Institut Pariwisata Trisakti, 2020)
The study aims to find out the solving method for problems in the thematic tourist village of Mulyaharja and designing the development of thematic tourism village model based on a community empowerment approach. This study is qualitative with an action research method. There are five respondents, i.e. chief of the village office, secretary of the village office, manager of the thematic tourist village, leader of mature farmer group and chief of youth group organization. This study was undertaken from February, 2018 to September, 2019. The generated outcomes are a solving problem method as solving steps chart, which consists of an explanation of the problem, solving and progress report each aspect, institutional, vision, activity, amenities, accesbility and entrepreneurship aspect. Furthermore, the model designed for development of thematic tourist village based on community empowerment is a circle with series of steps of eleven steps that connected each other and continuity. The series of steps are 1) choosing the candidate of partner village; 2) deciding the category of tourist village; 3) executing the MoU; 4) determining the program targets; 5) identifying the potentials of tourist village; 6) managing the empowerment programs; 7) implementing the assistance programs; 8) directing the college resources; 9) promoting the outcome of program; 10) evaluating the program and 11) mapping the stakeholder based on their proactive involvements. Keywords: Development, Thematic Tourist Village, Community Empowerment Approach